Koroshi no rakuin - Suzuki, Seijun, 1923-2017; Shishido, Jo, 1933-2020; Ogawa, Mariko; Mari, Annu, 1948-; Nanbara, Koji, 1927-2001 (Criterion collection, 1999)
Μια ταινία για επαγγελματίες δολοφόνους- η αποδόμηση του γκανγκστερικού είδους.